3D Printing - Dawn of a New Era in Learning Veterinary Anatomy - Sivagnanam (Indian Journal of Veterinary Anatomy, 2022)
Veterinary Anatomy is a discipline concerned with teaching and learning of three-dimensional structures of animal body. The Veterinary anatomy has historically been the cornerstone of all the disciplines of human medicine, veterinary and animal sciences. Traditional anatomy teaching methods consist of didactic lecture with chalk and talk, PPT presentations, prosection by teacher and dissection by student. This study is to reveal the current technology of teaching and learning by making 3D Anatomical specimens which would help both faculty and students to get rid of Carcinogenic formalin vapour both in the laboratories and museums. A novel method of CT scanning and creation of DICOM files for producing Raw rasterized data is found in this research. Also the obtained data are converted to STL (Standard Tessellation Language) files that are readily printable in any 3D Printer. ACanine humerus is printed using the new technology to demonstrate that all anatomy teaching models could be produced without quality compromise in future using FDM and SLA type of 3D Printers.Healthy living is the right of every human. In this context 3D printed learning aids are boon in pedagogy. The materials, methods and advantages of 3D prints of biological specimens over other techniques of Veterinary Anatomy teaching are discussed in this research.Adopting the 3D printing technology in making Veterinary Anatomy specimens is certainly a dawn of new era in learning Veterinary Anatomy.